A Numerical Study of Wave Propagation and Cracking Processes in Rock-Like Material under Seismic Loading Based on the Bonded-Particle Model Approach. (October 2022) - Zhang, Xiaoping; Zhang, Qi; Liu, Quansheng; Xiao, Ruihua
Abstract: An earthquake is usually followed by a considerable number of aftershocks that play a significant role in earthquake-induced landslides. During the aftershock, the cracking process in rocks becomes more complex because of the formation of faults. In order to investigate the effects of seismic loading on the cracking processes in a specimen containing a single flaw, a numerical approach based on the bonded-particle model (BPM) was adopted to study the seismic loading applied in two orthogonal directions. The results reveal that no transmission and reflection phenomena were observable in the small specimens (76 mm × 152 mm) because they were considerably smaller than the wavelength of the P-wave. Furthermore, under seismic loading, the induced crack was solely tensile in nature. Repeated axial seismic loading did not induce crack propagation after the first axial seismic loading. Cracks began to propagate only when the seismic loading direction was changed from axial to lateral, and then back to axial, ultimately resulting in the failure of the specimen.